EFEKTIVITAS MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA KOMIK DALAM MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI KEDUNGSARI 02 TAYU PATI - Azlin, Hafidza; Hilyana , F. Shoufika; Masfuah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the effectiveness of the project-based learning model assisted by comic media in improving the IPAS learning outcomes of fifth-grade students at SD Negeri Kedungsari 02 Tayu Pati. This method was implemented to create innovative and engaging learning by integrating a scientific approach. The research used a one-group pretest-posttest experimental design with 11 students over three sessions. The Wilcoxon test results showed significant differences between the pretest and posttest (understanding 0.003 < 0.05; process skills 0.003 < 0.05). The N-Gain test revealed a 73.1% increase in IPAS understanding and a 57.15% improvement in process skills. In conclusion, this model is effective in significantly enhancing student learning outcomes.